Technology Entrepreneurship Project (ENT 600) : Philips Malaysia / Nur Far’ain Irwani Mohd Nurfaridz - Mohd Nurfaridz, Nur Far’ain Irwani (2021)
Philips Koninklijke N.V. A Dutch multinational conglomerate corporation founded in Eindhoven (literally Royal Philips, usually shortened to Philips, stylized in its logo as PHILIPS) is a Dutch conglomerate corporation. It has had most of its headquarters in Amsterdam since 1997, but the Benelux headquarters are still in Eindhoven. Philips was once one of the world's largest electronics firms, now concentrating on healthcare technology, with the divestment of other divisions. It was founded by Gerard Philips and his father Frederik in 1891, with light bulbs being their first products. It currently employs about 74,000 employees in 100 countries. In 1998 , the company received its royal honorary title and in 2013 dropped the "Electronics" in its name, owing to its reorientation from consumer electronics to healthcare technology. Toaster is a small electrical device constructed by exposing the piece to high heat to create toast to bake a piece of bread. This appliance is capable of baking different types of sliced bread products. In 1893, and later through its growth throughout the years, the device was invented in Scotland, including the implementation of an automatic mechanism system to stop the burning and processing of bread slices. The toaster from Philips has new technology. Compared to several other branded toasters, this toaster has come a long way. This can be seen since distinct types and models are created by Philips toasters. This has shown that the toaster from Philips has the highest efficiency compared to toasters offered by other businesses.